Current «policies of knowledge» in the European Union : mapping and critically assessing «quality» in a «measurable» Europe of knowledge - Pasias, George K.; Roussakis, Yiannis E. (Revista Española de Educación Comparada, 2012)
This paper investigates the content and the different «dimensions» of «quality» in the current «policies of knowledge» of the European Union as they are specified by the renewed Lisbon Strategy and in the frame of the construction of a «measurable Europe of Knowledge». The study analyses critically the policy discourses and policy practices of the European Union from 1994 to 2010 using both primary (e.g. official documents) and secondary (e.g. scholarly articles, studies and research) sources. It consists of four sections: The first section refers to the current constructions of quality discourse in the European context (e.g. globalization, knowledge economies and GATS, new public management, new governance, etc.). In the second section, we examine the integration of «quality» in the EU’s discourses and policies (Treaties, Action Programs as well as in the general, vocational and higher education initiatives). The third section reviews the quality discourse in the context of the late EU’s policy processes (Lisbon, Bologna and Copenhagen). In the final section we put forward a critical reading of the «audit/ quality» nexus based on a «policy by numbers» technocratic-managerial rationale aiming at the construction of a measurable «Europe of knowledge». Este artículo investiga el contenido y las diferentes «dimensiones» de «calidad» en las actuales «políticas de conocimiento» de la Unión Europea, del modo en que están especificadas por la renovada «Estrategia de Lisboa» y en el marco de la construcción de una «Europa del Conocimiento Medible ». El estudio analiza en profundidad los discursos políticos y las prácticas políticas de la Unión Europea desde 1994 hasta 2010, utilizando a la vez fuentes primarias (por ejemplo, documentos oficiales) y secundarias (por ejemplo, artículos, estudios e investigación académicos). Consta de cuatro secciones: La primera sección se refiere a las actuales construcciones del discurso sobre la calidad en el contexto Europeo (por ejemplo, globalización, economía del conocimiento, la nueva gestión pública, nuevos gobiernos, etc.). en la segunda sección, examinamos la integración de la «calidad» en los discursos y políticas de la UE (Tratados, Programas de Acción así como las iniciativas generales, vocacionales de la educación superior). La tercera sección revisa el discurso de la «calidad» en el contexto de los actuales procesos políticos de la UE (Lisboa, Bolonia, Copenhague). En la última sección, presentamos una lectura crítica del nexo «auditoría/calidad», basado en una «política de los números», de objetivo tecnocrático-gerencial de la construcción de una «Europa del conocimiento» medible.